ARTIKEL REVIEW : AKTIVITAS ANTIOKSIDAN BUNGA MAWAR MERAH (Rosa damascene Mill.) - Oktavia, Dian Ayu; Aristia, Bella Fevi; Prajawanti, Kadeq Novita (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Red rose (Rosa damascena Mill.) is an ornamental plant that is rich in bioactive compounds such as flavonoids, anthocyanins, phenols, vitamin C, tannins, and saponins that function as natural antioxidants. The purpose of this article is to review research results related to the antioxidant activity of red rose flowers in various dosage forms and extraction methods. This review was conducted through a literature review of 10 selected scientific articles in the range of 2015-2025 using the exclusion and inclusion method. The results showed that most of the red rose flower extracts showed very strong antioxidant activity, characterized by IC₅₀ values < 50 ppm, even in some studies reaching < 20 µg/mL. Antioxidant activity is influenced by the type of solvent, temperature and processing time, as well as the combination of ingredients such as bengkoang or mint leaves. Polar extracts such as ethanol and methanol tend to give the best results, while high temperature treatment and long heating times tend to reduce the effectiveness of active compounds. Thus, rose red flowers have great potential as a source of natural antioxidants that can be utilized in functional food, cosmetic, and pharmaceutical products.